Proletariat Digital dalam Citizen Journalism: Kasus Kompasiana - Irma Elmira Husbuyanti (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
The trend of citizen journalism in Indonesia has increased since the emergence of amateur videos of the Aceh tsunami in 2004. This is considered as a momentum of new democracy in media because it allows public to independently produce and disseminate information without being intervened by agendasetting of mainstream media. The power of publication was seen to shift from mainstream media to personal ones. However, this trend of citizen journalism changed as it begun to be co-opted by mainstream media in the form of a user-generated content platform in 2008. This paper examines changes in citizen journalism which is managed by mainstream media by focusing on Kompasiana of Kompas Gramedia Group as its unit of analysis. Using Van Djik’s Critical Discourse Analysis and Marxist political economy of media as theoretical approach, it shows that the involvement of mainstream media in citizen journalism is not only seen as a collaboration, but also construction of digital labor. This can be explained by looking at three aspects of Kompasiana commodification practices: regulations, wages, and working hours.